Practice of oral hygiene and its relation to periodontal health status among female population with chronic periodontitis: a retrospective analysis - Yaacob, Munirah; Fazid, Nurul Farahin; So'odi, Siti Mahirah; Husain, Juzaily; Muhammad Ali, Suhaila (Zes Rokman Resources, 2019)
Chronic periodontitis is the second most common oral disease worldwide. At an individual level, personal oral hygiene practice remains an integral part of the prevention and control of periodontal diseases. The study was aimed to assess the relationship between oral hygiene practice of female population with chronic periodontitis and their periodontal health status. A retrospective data of 91 female with chronic periodontitis population that attended IIUM Dental Clinic was retrieved from patients’ case records from the year 2014 to 2017. ANOVA test was applied to infer the relationship between personal oral hygiene practice and the periodontal health status. Mean age for the group was 49.7±10.25, with the majority of them were Malays aged between 50 to 64 years old. All of them practice at least once a day brushing and lesser were flossing or used mouthwash as their daily oral care. ANOVA test showed the effect of cleaning more than once daily [F (2,88)= 3.37, p<0.05] and flossing [F (3,87)= 5.29, p<0.05] habits and frequency has significantly influenced the level of plaque scores. However, the analysis showed no significant relationship with other periodontal health parameters such as bleeding on probing, periodontal pocket depth, and missing teeth status. Oral hygiene practice found to influence the plaque control level in the female with chronic periodontitis. As plaque biofilm is one of the primary etiologies of periodontitis, it is essential to encourage the excellent practice of more than once brushing teeth daily and promoting flossing habit in patients suffering from chronic periodontitis.